Frequency of Thrombocytopenia and Heparin-Induced Thrombocytopenia in Patients Receiving Extracorporeal Membrane Oxygenation Compared With Cardiopulmonary Bypass and the Limited Sensitivity of Pretest Probability Score. Issue 5 (May 2020) - Arachchillage, Deepa R. J.; Laffan, Mike; Khanna, Sanjay; Vandenbriele, Christophe; Kamani, Farah; Passariello, Maurizio; Rosenberg, Alex; Aw, TC; Banya, Winston; Ledot, Stephane; Patel, Brijesh V.
Abstract : Objectives: To ascertain: 1) the frequency of thrombocytopenia and heparin-induced thrombocytopenia; 2) positive predictive value of the Pretest Probability Score in identifying heparin-induced thrombocytopenia; and 3) clinical outcome of heparin-induced thrombocytopenia in adult patients receiving venovenous- or venoarterial-extracorporeal membrane oxygenation, compared with cardiopulmonary bypass. Design: A single-center, retrospective, observational cohort study from January 2016 to April 2018. Setting: Tertiary referral center for cardiac and respiratory failure. Patients: Patients who received extracorporeal membrane oxygenation for more than 48 hours or had cardiopulmonary bypass during specified period. Interventions: None. Measurements and Main Results: Clinical and laboratory data were collected retrospectively. Pretest Probability Score and heparin-induced thrombocytopenia testing results were collected prospectively. Mean age (± SD) of the extracorporeal membrane oxygenation and cardiopulmonary bypass cohorts was 45.4 (± 15.6) and 64.9 (± 13), respectively ( p < 0.00001). Median duration of cardiopulmonary bypass was 4.6 hours (2–16.5 hr) compared with 170.4 hours (70–1, 008 hr) on extracorporeal membrane oxygenation. Moderate and severe thrombocytopenia were more common in extracorporeal membrane oxygenation compared with cardiopulmonary bypass throughout ( p < 0.0001). Thrombocytopenia increased in cardiopulmonary bypass patients on day 2 but was normal in 83% compared with 42.3% of extracorporeal membrane oxygenation patients at day 10. Patients on extracorporeal membrane oxygenation also followed a similar pattern of platelet recovery following cessation of extracorporeal membrane oxygenation. The frequency of heparin-induced thrombocytopenia in extracorporeal membrane oxygenation and cardiopulmonary bypass were 6.4% (19/298) and 0.6% (18/2, 998), respectively ( p < 0.0001). There was no difference in prevalence of heparin-induced thrombocytopenia in patients on venovenous-extracorporeal membrane oxygenation (8/156, 5.1%) versus venoarterial-extracorporeal membrane oxygenation (11/142, 7.7%) ( p = 0.47). The positive predictive value of the Pretest Probability Score in identifying heparin-induced thrombocytopenia in patients post cardiopulmonary bypass and on extracorporeal membrane oxygenation was 56.25% (18/32) and 25% (15/60), respectively. Mortality was not different with (6/19, 31.6%) or without (89/279, 32.2%) heparin-induced thrombocytopenia in patients on extracorporeal membrane oxygenation ( p = 0.79). Conclusions: Thrombocytopenia is already common at extracorporeal membrane oxygenation initiation. Heparin-induced thrombocytopenia is more frequent in both venovenous- and venoarterial-extracorporeal membrane oxygenation compared with cardiopulmonary bypass. Positive predictive value of Pretest Probability Score in identifying heparin-induced thrombocytopenia was lower in extracorporeal membrane oxygenation patients. Heparin-induced thrombocytopenia had no effect on mortality. Abstract : Supplemental Digital Content is available in the text.